Peningkatan Nilai Overall Equipment Effectiveness Pada Industri Otomotif di Indonesia Menggunakan Metode SMED - Suhendra Suhendra; Tri Ngudi Wiyatno (Prosiding Sains dan Teknologi, 2022)
Indonesia Car sales in Indonesia for the domestic market and CBU (Completely Built Up) export until the end of 2021 have increased by 35% compared to the previous year, when the spread of the corona virus was still very high. This fact indicates that people's purchasing power after the COVID-19 pandemic has gradually increased significantly. This gives a positive signal for each OEM (Original Equipment Manufacturer) and automotive component suppliers to increase their productivity. Reducing downtime on a car production line is one way to increase productivity. Stamping is the first production process in car assembly, therefore it is very important to reduce downtime that occurs so that the OEE (Overall Equipment Effectiveness) of the engine increases. This study aims to determine the factors that cause the decrease in OEE value on the 800T stamping machine at PT XYZ and reduce downtime when dies change over time. By using the SMED (Single Minutes Exchange of Dies) method, downtime at the time of changing dies can be reduced from 17.1 minutes to 11.2 minutes, so the OEE value of the stamping machine can increase from 62.4% to 78.2%. Keywords: Overall Equipment Effectiveness, Stamping, Single Minutes Exchange of Dies